(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2025)
This study explores the pedagogical conditions essential for shaping the process of liberating students from negative ideas that hinder their intellectual and moral development. Negative ideas, including prejudices, stereotypes, and harmful social beliefs, can impede critical thinking and personal growth. The paper examines how critical pedagogy, reflective learning, and supportive educational environments can foster students’ ability to recognize, question, and overcome such ideas. Employing a mixed-methods approach, including literature review and qualitative research in secondary schools, the study identifies key conditions such as teacher competence, dialogic classrooms, curriculum inclusiveness, and institutional support that contribute to this process. The findings highlight the importance of empowering students to develop positive thinking and resilience against negative ideological influences.